Pandeglang Regency Regional Government Strategy in Digitalizing Micro, Small and Medium Enterprises (MSMEs) Product Marketing - Sanjaya, Natta; Lukman Hakim, Agus; Hadiono, Ade; Destiana, Destiana (Journal of Education on Social Science (JESS), 2024)
At this time there are still many business actors who market their products manually. Based on data and information from the Department of Agriculture and Food Security, the Department of Fisheries, the Department of Tourism and Culture as well as from the Department of Cooperatives, MSMEs, Industry and Trade of Pandeglang Regency, that of the 20 MSMEs considered as Leading MSMEs, only 3 (three) MSMEs or only 15% are selling online. The purpose of this research is to identify the leading MSME products in Pandeglang Regency, and to find out the strategies and steps for utilizing digital platforms in marketing MSME products in Pandeglang Regency. The research approach used is mixed methods. The analysis technique used uses quantitative descriptive analysis techniques. Researchers conducted data validity testing through triangulation and member checking and qualitative data analysis techniques using interactive data analysis. Based on descriptive analysis, it can be identified that the economy of Pandeglang Regency excels in the Agriculture Sector, Fisheries Sector and Tourism Sector. Utilizing digital marketing for superior MSME products is by knowing the target product market, optimizing the website, being active on social media, using quality content, using e-mail marketing, using online advertising, easy access to online purchases, using data analysis, collaborating with influencers. Local, Focus on Customer Engagement, Performance Monitoring and Evaluation. In relation to the recommendations needed by Pandeglang MSMEs and those that are in accordance with Pandeglang Superior Products are the WhatsApp, Facebook, Instagram and TikTok platforms.